Electronic Structure and Lattice Vibrations of Ca2CuO2Cl2: a hybrid density functional study - PATTERSON, CHARLES (My University, 2008)
The electronic structure and phonon modes of Ca 2 CuO 2 Cl 2 have been calculated using hybrid density functional theory HDFT methods. The material is correctly predicted to be an antiferromagnetic insulator with a band gap of around 2 eV. Lattice parameters and atomic positions are in good agreement with experi- ment with a maximum error in lattice constant less than 2%. Phonon modes were calculated using HDFT Hamiltonians containing Hartree-Fock HF exchange with weights of 0.2, 0.3, or 0.4. Phonon mode frequen- cies typically shift upward by 4% on increasing the HF exchange weight by 0.1. Computed Cu-O stretching modes of E u symmetry at 615 and 334 cm −1 are in good agreement with recently reported IR absorption frequencies at 620 and 350 cm −1 .
PUBLISHED
Keywords: Physics